Improving Learning Outcomes Through the Use of Media STEM Based in Volcano Eruption Simulation in the Theme of Natural Events - Anik Twin Twiningsih (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
The objective of the study is to reveal the improvement in student learning outcomes in the use of instructional media teaching aids on STEM-Based Volcano Eruption Simulation (Science, Technology, Engineering, Mathematics) on the theme of Thematic Class I learning natural events. This research was conducted on first-grade students of Public Elementary School of Laweyan Surakarta City in the Second Semester of 2018/2019 Academic Year. The number of students was 25 students, consisting of 8 male students and 17 female students. The study was a Classroom Action Research (CAR) with patterns: planning, implementing, observing, reflecting, revising. The data were collected through the method of discussion, observation, tests, field notes, and documentation. Based on the results of the study, it was found that student learning outcomes had increased learning outcomes, they were, the first cycle (79.60%) and the second cycle (84.00%). The study was concluded as through the use of instructional media for teaching aids of STEM-Based Volcano Eruption Simulation (Science, Technology, Engineering, Mathematics) on the theme of natural events Class I can improve the learning outcomes of Class I students of Public Elementary School of Laweyan Surakarta City Semester II in the Academic Year of 2018/2019.